PROFESSIONAL COMPETENCE OF AN EDUCATOR AND ITS IMPORTANCE IN TEACHING (Academia Science Repository, 2023)
The comprehensive prosperity, progress of society depends on the development of education and the improvement of content. Today, improving the quality efficiency of education is considered one of the most pressing issues. Any novelty that penetrates into human life awakens in it alertness, even dissatisfaction. Accordingly, educators who have been working with traditional methods for many years, are required to organize classes on the basis of state educational standards, which are improved as it is today. To do this, it is first necessary to radically change the professional consciousness of the teacher. This article provides feedback and insights into the professional competence of the educator and its importance in teaching.